Printability and particle packing of 3D-printable limestone calcined clay cement composites. (3rd May 2021) - Long, Wu-Jian; Lin, Can; Tao, Jie-Lin; Ye, Tao-Hua; Fang, Yuan
Graphical abstract: Highlights: Particle packing of quaternary composites was optimized for favorable printability. Rheological behaviors of composites were studied for evaluating the printability. High thixotropy of LC3 was found to be effective for buildability. A novel low-carbon and low-energy printable composite was proposed. Abstract: This study develops a modified limestone calcined clay cement (LC3) composite for 3D printing, by introducing silica fume (SF) and particle packing theory. Interactions between particle packing density, rheological properties, and printability of the composites were synergistically investigated. Moreover, the ratio of the sand-to-binder (S/B) was also analyzed to explore the performance response. Results show that when composites contain 33.33 wt% calcined clay, 16.67 wt% limestone powder and 5 wt% SF with S/B ratio of 2.5, the dynamic yield stress, static yield stress, and structural recovery can be significantly improved. The proposed mortar can be continuously extruded with few defects and exhibited an excellent shape retention during printing process. Furthermore, the embodied energy (EE) and embodied carbon emissions (ECO2 e) per cubic meter of optimal mortar respectively decreased by 50.2% and 45.2% with respect to the plain mortar. Finally, the employment of LC3 containing SF together with optimum particle packing system mutually contributed to lower the cement content of composites that eventually led to the development of eco-efficient printable materials.